Pengaruh Rasio ROA, ROE Terhadap Pertumbuhan Laba Pada Perusahaan Pertambangan Yang Terdaftar Dalam Jakarta Islamic Index Tahun 2018-2022 - Ahmad Syapari; Eja Armas Hardi; Ahmad Syahrizal (Universitas Kristen Indonesia Toraja, 2023)
This research leads to the Effect of the Ratio of Roa, Roe on Profit Building in Mining Companies Listed in the Jakarta Islamic Index for 2018-2022. The benefit of this research is to find out whether there is an effect of the Roa, Roe Ratio on Profit Growth in Mining Companies Registered in the Jakarta Islamic Index for 2018-2022. The analytical method used in this study is panel data regression. and processed data used in this study by utilizing Eviews 12 and Microsoft Excel 2010 software. The sampling method used was purposive sampling, namely by considering several criteria specified in this research. The research results show that Roa has an effect on profit growth and Roe has no effect on profit growth, while together (simultaneously) Roa and Roe have an effect on profit growth in mining sector companies in JII 2018-2022Keywords: net income, total assets and share price